Experiments on the bearing capacity of aeolian sand stabilized by cement stabilizers - Mingqiang Sheng; Chun Zou; Zengzhen Qian; Xianlong Lu (地质科技通报, 2022)
Aeolian sands are inherently very low in strength and very poor in stability. By using local sources according to local conditions, aeolian sand stabilization with cement may be an alternative method to improve the mechanical characteristics of aeolian sand in desert areas. In this study, shear, compression and uplift bearing capacity tests were carried out on the cement-stabilized aeolian sand with 3% water content by using aeolian sand collected from the Kubuqi Desert of Inner Mongolia. The results show that cement stabilization has a much greater enhancement on the cohesive strength than that of the inner frictional angle. After 28 days of normal temperature curing, the average unconfined compressive strength of the stabilized aeolian sand with 3% water content and 6% cement content is 0.156 MPa. The uplift load-displacement curve of stabilized aeolian sand shows a two-stage change law from the initial elastic section to the peak load and failure after the peak load, which has obvious brittle failure characteristics. The results show that the uplift capacity of aeolian sand stabilized by cement is related to the foundation slab size, uplift embedment, and the ratio of uplift embedment to foundation slab width.